STEM ACTIVITIES WITH PRESCHOOLERS: PRE-SERVICE EARLY CHILDHOOD TEACHERS’ EXPERIENCES - Khalsa , Balvinder Kaur (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study aims to explore the experiences of pre-service early childhood education (ECE) teachers in conducting STEM activities with preschoolers. This study employed a combination of quantitative and qualitative approaches to collect the data. Questionnaires were distributed to 19 pre-service early childhood education (ECE) teachers who were involved in STEM activities with preschoolers. The findings showed that 68.4% of them had no idea what STEM was, even during their secondary education, and 73.3% of them were quite confused about STEM before they took the Science and Technology course. SPSS indicated a high mean value of 4.32, suggesting that pre-service (ECE) teachers felt fulfilled and happy conducting STEM activities with preschoolers. A mean value of 4.11 indicated an increased confidence level among the teachers in carrying out STEM activities. Qualitatively, semi-structured interviews were conducted to gather information and understand the teachers' experiences during STEM activities. Pre-service (ECE) teachers reported that STEM activities improve their self-confidence in executing them, they are practical and engaging for preschoolers, and concurrently enhance problem-solving, through the combination of science, technology, mathematics and engineering elements. In conclusion, STEM activities are fun, integrated, and uncomplicated, while promoting holistic development in young children. The experience gained positively enhanced the teachers' knowledge of STEM and increased hands-on, yet exciting opportunities for the preschoolers.